Il martirio di Teodoro Gabras (BHG 1745) - Rigo, Antonio (Analecta Bollandiana, 1998)
The article re-examines all the available information about the life and martyrdom of Theodore Gabras († 1098-1108 ca.). The study of a synaxarion notice written in his honour and preserved in a now-lost 18th century manuscript enables us to replace the eventual existence of Theodore in the politico-military reality of eastern Anatolia of the 11th and 12th centuries.